The Dynamics of Land Ownership Rights under Indonesian Agrarian Law: Legal Certainty and the Challenges of Social Justice - Lutfi Effendi; Subianta Mandala (al-Battar: Jurnal Pamungkas Hukum, 2025)
Land ownership rights constitute the strongest, fullest, and hereditary form of land rights within the Indonesian agrarian legal system as regulated by Law Number 5 of 1960 concerning Basic Agrarian Principles (the Basic Agrarian Law). In practice, however, the regulation and implementation of land ownership rights have undergone significant dynamics influenced by regulatory developments, socio-economic conditions, and national land policies. Agrarian reform initiatives and sectoral regulatory changes are intended to promote legal certainty and equitable land distribution, yet they simultaneously give rise to complex legal issues, including agrarian conflicts, overlapping land titles, uncontrolled land conversion, and the proliferation of land mafia practices. This study aims to examine the legal position and characteristics of land ownership rights within Indonesian agrarian law, analyze the development of the regulatory framework governing such rights, and identify the principal challenges in achieving legal certainty and social justice for land rights holders. The research employs a normative juridical method using a statutory and conceptual approach, supported by a literature review of relevant legislation, scholarly books, and academic journals, with particular reference to the Basic Agrarian Law and Government Regulation Number 24 of 1997 on Land Registration. The findings indicate that although the existing legal framework is designed to provide legal protection and certainty through land registration mechanisms, its implementation remains constrained by institutional weaknesses and enforcement gaps. Accordingly, the study underscores the necessity of strengthening land administration systems, reforming agrarian regulations to respond to contemporary social and economic developments, and enhancing law enforcement to ensure that land ownership rights function not only as instruments of legal certainty but also as vehicles for social justice and sustainable development in Indonesia.